A DESCRIPTIVE ANALYSIS OF TEACHER’S QUESTIONING STRATEGIES IN IMPROVING ENGLISH CLASSROOM INTERACTION FOR JUNIOR HIGH SCHOOL STUDENTS - Dwi Kurniawati; Sugeng Susilo Adi (Erudio Journal of Educational Innovation, 2021)
Questioning is the key means by which teachers find out what pupils already know, identify gaps in knowledge and understanding and scaffold the development of their understanding to enable them to close the gap between what they currently know and the learning goals. Questioning Strategy is also used to motivate students in a learning process. During the teaching process, teachers of SMPN 3 Rejoso Junior High Scholl applied the questioning strategy to improve students’ comprehension. Considering that reason, this research was intended to know what is the questioning strategy applied by teachers in learning English. This study was conducted using qualitative research design. The instrument used was interview. The respondents of this research were three English teachers and ten students from second and third grade in various level of proficiency in English lesson. The result of this study shows that the applications of questioning strategy gave positive Impacts for teachers and students. English teachers agreed that questioning strategy is useful to help students active in learning process and also build the students’ motivation in learning English. The main obstacle faced is language barrier and students’ lack of awareness to study English. Almost all students agreed that the questioning strategy had a good effect. The students found the teacher’s strategy very interesting and effective to build their motivation.